1992
DOI: 10.1002/jbmr.5650070909
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and progesterone replacement therapy reduces glucocorticoid-induced bone loss

Abstract: This is a retrospective study of 15 postmenopausal or amenorrheic women aged 34-78 years who had taken prednisone for 6-108 months and were followed for 1 year while continuing to take doses of 5-15 mg/day. A total of 8 patients were treated with 0.6256 mg Premarin daily for 25 days and 5 mg/day of medroxyprogesterone on days 15-25 (ERT, group 2); 7 were followed without ERT (group 1). A group of 17 women, matched for age, were randomly selected from our computerized data base to serve as a control group (grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…The aim of the current study was to investigate if addition of Ral or E2 to ovariectomized Dex-treated arthritic mice could prevent bone loss while simultaneously ameliorating the arthritic disease. In clinical trials, the addition of estrogen replacement therapy has been shown to have positive effects on arthritis-associated and glucocorticoid-induced bone loss [8,29,30]. In addition, we have previously shown that treatment with the combination of Dex + E2 have additive suppressive effects on the T cell-mediated delayed type hypersensitivity reaction in mice [31].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the current study was to investigate if addition of Ral or E2 to ovariectomized Dex-treated arthritic mice could prevent bone loss while simultaneously ameliorating the arthritic disease. In clinical trials, the addition of estrogen replacement therapy has been shown to have positive effects on arthritis-associated and glucocorticoid-induced bone loss [8,29,30]. In addition, we have previously shown that treatment with the combination of Dex + E2 have additive suppressive effects on the T cell-mediated delayed type hypersensitivity reaction in mice [31].…”
Section: Discussionmentioning
confidence: 99%
“…In a subgroup analysis of 42 women from a study of 200 post-menopausal women with rheumatoid arthritis who were receiving lowdose GCs, HRT recipients had a significant increase in lumbar spine BMD relative to controls although femoral neck BMD was not significantly changed in either group [119]. Twelve months of treatment with testosterone injections significantly increased mean lumbar spine BMD by 5% relative to controls in 15 men with asthma receiving GCs [120].…”
Section: Hormone Replacement Therapymentioning
confidence: 95%
“…Estrogen replacement clearly reduces bone mineral density losses in women treated concurrently with glucocorticoids 35 . Therefore, if a woman is otherwise unable to take an osteoporosis-specific prescription treatment or if a patient is already on estrogen treatment, estrogen therapy could be considered or maintained.…”
Section: Prevention and Treatment Of Glucocorticoid Induced Osteoporosismentioning
confidence: 97%